Cost effectiveness of ulcerative colitis treatment in Germany: a comparison of two oral formulations of mesalazine - Mittendorf Thomas; Yen Linnette; Prenzler Anne; von der Schulenburg J-Matthias (BMC, 2011)
Abstract Background The treatment of ulcerative colitis (UC) can place a substantial financial burden on healthcare systems. The anti-inflammatory compound 5-aminosalicylic acid (5-ASA; mesalazine) is the recommended first-line treatment for patients with UC. In this analysis, the incremental cost effectiveness ratio (ICER) of two oral formulations of 5-ASA (Mezavant® and Asacol®) is examined in the treatment of patients with mild-to-moderate, active UC in Germany. Methods A Markov cohort model was developed to assess the cost effectiveness of Mezavant compared with Asacol over a 5-year period in the German Statutory Health Insurance (SHI). Drug pricing details for 2009 were applied throughout the model, and overall resource use was determined and also fitted to 2009 from published results of a large cross sectional study of German SHI patients. Cost per quality adjusted life year (QALY) was the primary endpoint for this study. Remission rates were obtained using data from a randomised, phase III trial of Mezavant with an active Asacol reference arm and a long-term, open label, safety and tolerability trial of Mezavant. Uncertainty in the study model was assessed using one-way and probabilistic sensitivity analyses applying a Monte Carlo simulation. Results Over a 5-year period, healthcare costs for patients receiving Mezavant were 624 Euro lower than for patients receiving Asacol. Additionally, patients receiving Mezavant gained 0.011 QALYs or 18 more days in remission compared with Asacol. One-way sensitivity analyses suggest that these results are driven by both differences in the acquisition cost between mesalazine formulations and differences in treatment efficacy. Furthermore, sensitivity analyses suggest a probability of 76% for cost savings and higher QALYs with Mezavant compared with Asacol. If adherence and its influence on the remission rates and the risk of developing colorectal cancer were included in the model, the results might have even been more favorable to Mezavant due to its once daily dosing regimen. Conclusions This model suggests that patients treated with Mezavant may achieve increased time in remission and higher QALYs, with lower direct costs to the SHI when compared with Asacol. Mezavant may therefore be a suitable first-line option for the induction and maintenance of remission in UC.